2016
DOI: 10.1109/jlt.2016.2578463
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Loss and Broadband MMI-Based Multi/Demultiplexer in Si3N4/SiO2Technology

Abstract: A low-loss and broadband multimode interference (MMI)-based wavelength multi/demultiplexer in Si 3 N 4 /SiO 2 technology for erbium-doped lasing and amplifying applications is presented. The structural parameters of a 2 × 1 Si 3 N 4 MMI multi/demultiplexer are optimized to minimize losses. The design and analysis of the MMI multi/demultiplexer are carried out using a hybrid approach, which combines a modified effective index method, the 2D film mode matching method, and the 2D beam propagation method, with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…The fabricated waveguides have a width of W P 1.4 0.08 μm and a measured propagation loss of 0.14 dB/cm at the wavelength of 1532 nm, measured using reference add-drop ring resonators. Multi/ demultiplexers for combining/splitting the pump and signal modes were integrated on the passive Si 3 N 4 waveguides [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fabricated waveguides have a width of W P 1.4 0.08 μm and a measured propagation loss of 0.14 dB/cm at the wavelength of 1532 nm, measured using reference add-drop ring resonators. Multi/ demultiplexers for combining/splitting the pump and signal modes were integrated on the passive Si 3 N 4 waveguides [40].…”
Section: Resultsmentioning
confidence: 99%
“…The characterization used the same experimental setup as the work of Ref. [40]. By launching the signal light through the signal (S) port and pump (P) port, the MMI losses were measured to be 1.38 0.1 dB and 9.03 0.04 dB at the wavelength of 1532 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different properties discussed above have made Si 3 N 4 an ideal candidate for the realization of a various linear and non-linear PICs spanning from visible to mid-infrared wavelengths. Si 3 N 4 has been widely used to demonstrate passive linear devices for datacom and visible wavelengths [89,90], including low loss waveguides [90,91], multimode splitters [83,92] and Mach-Zehnder interferometers [93]. Many research groups have worked on (de)multiplexers such as array waveguide gratings [94], angled-multimode interferometers [95,96] and echelle gratings [94,97].…”
Section: Silicon Nitridementioning
confidence: 99%
“…Frandsen et al experimentally showed a drop-filter with 11 nm full-width-half-maximum (FWHM) [12], but the device only filters out one wavelength over a larger footprint than we demonstrate here. Recent experimental demonstrations of multimode interference (MMI) devices have also achieved demultiplexing capabilities in ultracompact footprints but again with large channel spacings over two channels [13,14]. Since the number of wavelengths available in a WDM system is inversely proportional to the channel spacing, WDM systems that utilize multiple wavelengths require demultiplexers with more channels and much smaller channel spacing.…”
Section: Introductionmentioning
confidence: 99%